Evaluation of laboratory equipments as channel sounding system for mobile radio propagation - Lee, Yee Hui (2013)
This paper reports a feasibility study of using common laboratory equipments as sounding system for mobile radio-propagation measurements. Comparing to our existing system, good performance is achieved. Therefore, the dependence of channel measurements on specific sounders is reduced. However, proper channel sounder should be selected based on the application environments.